Youth Perceptions and Motivations Towards Entrepreneurship in Egypt and Their Policy Implications: A Qualitative Study - Hassan, Yara Ali (AUC Knowledge Fountain, 2023)
Entrepreneurship is one of the key driving forces for economic development. The entrepreneurship ecosystem in Egypt has been growing exponentially whereas a large number of public and private institutions have been established to support young entrepreneurs to start their own business. Despite of the growing attention towards entrepreneurship, few studies have investigated the real motives of Egyptian youth who decided to join the entrepreneurship field. Thus, this study aims to advise policy makers through studying youth perceptions and motives towards entrepreneurship and the underlying factors that shape their perceptions. The study has been conducted using a qualitative approach and purposive sampling has been applied during the data collection process. Research data has been collected through face to face and phone interviews and was analyzed to generate thematic findings. Three themes have been conceptualized to explain perceptions and motives of Egyptian youth towards entrepreneurship. Findings showed that entrepreneurship is viewed by youth as a “new social trend”, “an alternative to the limited employment opportunities in the labor market and a means of “utilizing market opportunities that comes with a number of cultural, financial, and legal challenges”. Based on research outcomes, some key recommendations have been provided for the consideration of implementers and policy makers such as integration of hands-on experience in the entrepreneurship trainings, inclusion of entrepreneurship education in the general education system and facilitating access to finance for small startups.